Pengembangan Media Video Animasi mengenai Pola Makan untuk Pencegahan Diabetes Melitus pada Remaja Kelas 7 di SMP PGRI 4 Cimahi - Nurmadini, Meinisya; Iryanti (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Diabetes mellitus is becoming more prevalent not only among adult but also among adolescents, contributing to high mortality rate in this age group In West Java alone 12,806 cases of Diabetes Mellitus in adolescents aged 5-14 years, with 675 cases in Cimahi City. A poor diet, often due to a lack of awareness and information, is a primary cause. Health education through animated videos is necessary, as it is effective and engages multiple senses. Research Puposes: To design and assesss the feasibility of an animated video about dietary habits aimed at preventing Diabetes Melitus among 7th grade students at SMP PGRI 4 Cimahi. Methodology: This R&D implements the 4D media development model (Define, Design, Development, Disseminate). The research involved 177 seventh-grade students from SMP PGRI 4 Cimahi. In the qualitative phase, 7 students were chosen using purposive sampling, and data were collected through interviews. For the quatitative research, the study included one material expert, one media expert, and 64 adolescent, who were selected based on the slovin formula with proportionate simple random sampling. Data were gathered through a media feasibility questionnaire, and the analysis was conducted using the percentage of feasibility and the average score. Results: Feasibility test results showed 78% approval from material experts, 98% from media experts, and 91% from the target group. Conclusion: Animated video media about diet as an educational tool for preventing Diabetes Mellitus is feasible and highly suitable for use.